The other option : NGO's and people's praxis - Ahmad, Mohiuddin, 1952-; Community Development Library (Dhaka, Bangladesh) (Dhaka : Community Development Library, 2000)
Contributed articles on the initiatives, policies and problems of NGOs in Bangladesh.
Machine generated contents note: Disaster Management -- Muhammad Saidur Rahman -- Sustainable Management of Environment -- Mahfuzul Haque -- Microfinance: Impacts, Constraints and Potentialities -- Sukhendra Kumar Sarkar and Faruque Ahmed -- Legal Aid -- Salma Sobhan -- Research and Documentation: -- A Look at the NGO Sector -- Harun-ur-Rashid and Kazi Mustak Gausul Hoq -- Sustainablity of NGOs: The Perspectives of BRAC -- Salehuddin Ahmed and M. Ghulam Sattar -- The NGO Mixture: Seeking the Perfect Ingredient -- Saira Rahman Khan -- State and the Civil Society -- Mohiuddin Ahmad.
Includes bibliographical references.
Keywords: Non-governmental organizations -- Bangladesh; Economic assistance -- Bangladesh; Bangladesh -- Economic conditions; Bangladesh -- Social policy